A hybrid algorithm using the FEM-MESHLESS method to solve nonlinear structural problems. (July 2022) - El Kadmiri, Redouane; Belaasilia, Youssef; Timesli, Abdelaziz; Kadiri, M. Saddik
Abstract: In this paper, we present a hybrid numerical development to solve two-dimensional nonlinear structural problems. The proposed approach was developed by combining weak and strong formulations and using a High-Order Development, Continuation technique and Hybrid approximation (HODC-HYB). The hybrid approximation is based on meshless strong form method and Finite Element Method (FEM). This algorithm allows us to overcome several drawbacks such as the difficulties of implementing meshless strong form methods near the boundary of the structural domain, meshless methods can be unstable and less precise for problems with Neumann boundary conditions, but these methods can overcome the connectivity technique and numerical integration in a big part of the domain. Numerical tests are carried out to demonstrate the reliability and the performance of the proposed algorithm by setting up a comparative study with the solutions obtained by HODC-FEM and HODC-MESHLESS algorithms, which are based on the weak and strong forms, respectively.